Etika Administrasi Pada Peningkatan Pelayanan Publik Yang Berkualitas Oleh Aparatur Di Kantor Desa Tegalrejo Kecamatan Dringu - Dini Ayu Permata Sari; Ainul Yaqin; Imam Sucahyo (INTELEKTUAL ( E-Journal Administrasi Publik dan Ilmu Komunikasi ), 2024)
Government service activities are related to the apparatus. The apparatus is required to perform services and organize tasks with a code of ethics. The code of ethics is a reference for action and understanding the values that are relevant to personal character. The ethics that need to be oriented to the government is the ethics of state administration. Such as public services by the apparatus in Tegalrejo Village, DringuSubdistrict, which must carry out services to the public and fulfill the elements that can serve the needs of Tegalrejo villagers. This is interesting to do research, related to administrative ethics on improving quality public services by the apparatus in the Tegalrejo Village Office, DringuSubdistrict. The results showed that administrative ethics were applied to improve quality public services by the apparatus at the Tegalrejo Village Office in Dringu Sub-district. Including aspects of efficiency in resources and funds that are utilized for the benefit of Tegalrejo villagers. The effectiveness aspect relates to the suitability of the ability and knowledge of the village apparatus in organizing services for the benefit of villagers. Aspects of service quality relate to friendliness and communicativeness, and timeliness in accordance with the conditions of the villagers and techniques that are easily accepted and understood by the villagers. The responsiveness aspect relates to the readiness and willingness of the apparatus to act with superior programs. The accountability aspect relates to the actions of the apparatus in services relevant to SOPs, regulations and policies.Research with qualitative type with interview techniques, observation, and documentation.